Nephroprotective Effect of Turkesterone Against Daunorubicin-Induced Acute Kidney Injury in Rats - Alaa R. Khudhair; Oleiwi, Mohammed Abdulameer; Khudhair, Asraa Radhi (Iraqi Journal of Pharmaceutical Sciences, 2025)
Turkesterone, a phytoecdysteroid that possessing an 11-α-hydroxyl group, is an analogue of 20-hydroxyecdysone which is an insect steroid hormone. Phytoecdysteroids, a group of ecdysteroid hormones naturally in plant species Ajuga turkestanica, Rhaponticum carthamoides Willd. and Cyanotis arachnoidea C.B.Clarke that centuries used due to their tonifying, adaptogenic, and antioxidant and ability to enhance physical performance. ecdysterone and turkesterone have been associated with different biological effects, as neuroprotective, anabolic, antihyperlipidemic and antidiabetic. Several studies suggested that the mechanism of DNR-induced cardiotoxicity and nephrotoxicity by the formation of the reactive oxygen species (ROS) through their anthracycline–iron complexes redox cycling as well as of their aglycones that is the principal mechanism that induces their cellular damage. This study designed in order to investigate the possible nephron-protective of Turkesterone, against the nephrotoxicity induced by Daunorubicin. Twenty-four (24) adult Sprague- Dawley female rats. The animals divided to four (4) groups of six (6) rats for each: Group Ӏ: received oral daily dose of 10% dimethyl sulfoxide (DMSO) (4 ml/kg) for 15 consecutive days. Group ӀӀ: received single daily oral dose of 10% dimethyl sulfoxide (DMSO) for 15 days, then subsequently received Daunorubicin 20 mg/kg for the last 3 days with a cumulative dose of (60 mg/kg) by IP injection. Group ӀӀӀ: received oral dose of Turkesterone (5mg/kg/day) for 15 consecutive days. Group ӀV: received oral dose of Turkesterone (5mg/kg/day) for 15 consecutive days, then subsequently received Daunorubicin 20 mg/kg for the last 3 days with a cumulative dose of (60 mg/kg) by IP injection. Nephrotoxic rats, with daunorubicin, pretreated with Turkesterone (Group ӀV) was showed significantly decline in the serum level of both urea and creatinine, also reversed oxidative stress markers; rat Glutathione peroxidase 4 levels, to the control level. Suppression of the apoptotic and inflammatory markers, by measuring rat interleukin 6 levels and rat cleaved caspase-3 levels respectively, in kidney tissues.